Criminal Justice System Outcomes for Buyers, Sellers, and Facilitators of Commercial Sex in Houston, Texas - Updegrove, Alexander H. (Crime & delinquency, 2019)
This study draws upon the economic model of prostitution to explore the relationship between gender, prostitution role, and criminal justice system outcomes. Official court data for 1,027 prostitution arrestees from Harris County (Houston), Texas, were used to differentiate participants by their role in the commercial sex trade (buyer, facilitator, or seller). Logistic regression results indicate that gender differences persist for case dismissal and plea deal acceptance among prostitution arrestees even after controlling for their criminality and role in the prostitution offense. Although gender does not influence the likelihood of conviction, buyers are significantly less likely to be convicted than sellers. Implications from these findings, as well as limitations and suggestions for further research, are discussed.